Endothelial Activin Receptor-Like Kinase 1 (ALK1) Regulates Myofibroblast Emergence and Peritubular Capillary Stability in the Early Stages of Kidney Fibrosis - Martínez-Salgado, Carlos; Sánchez-Juanes, Fernando; López-Hernández, Francisco J.; Muñoz-Félix, José M. (Frontiers in Pharmacology, 2022)
Renal tubulo-interstitial fibrosis is characterized by the excessive accumulation of extracellular matrix (ECM) in the tubular interstitium during chronic kidney disease. The main source of ECM proteins are emerging and proliferating myofibroblasts. The sources of myofibroblasts in the renal tubular interstitium have been studied during decades, in which the epithelial contribution of the myofibroblast population through the epithelial-to-mesenchymal (EMT) process was assumed to be the major mechanism. However, it is now accepted that the EMT contribution is very limited and other mechanisms such as the proliferation of local resident fibroblasts or the transdifferentiation of endothelial cells seem to be more relevant. Activin receptor-like kinase 1 (ALK1) is a type I receptor which belongs to the transforming growth factor beta (TGF-β) superfamily, with a key role in tissue fibrosis and production of ECM by myofibroblast. Predominantly expressed in endothelial cells, ALK1 also plays an important role in angiogenesis and vessel maturation, but the relation of these processes with kidney fibrosis is not fully understood. We show that after 3 days of unilateral ureteral obstruction (UUO), ALK1 heterozygous mice (Alk1+/−) display lower levels of kidney fibrosis associated to a lower number of myofibroblasts. Moreover, Alk1+/− mice have a lower degree of vascular rarefaction, showing improved peritubular microvasculature after UUO. All these data suggest an important role of ALK1 in regulating vascular rarefaction and emergence of myofibroblasts.